Stress management from Islamic and Western perspectives: a psycho-analytical approach - Kazeem, Bakare; Hashim, Che Noraini (LAP Lambert Academic Publishing, 2011)
Occupational stress is a pervasive phenomenon in the workplace. Its likely occurrence can be attributed to the discrepancies between occupational demands/responsibilities on the one hand, and worker's capabilities, needs or resources on the other. This book examines the sources of occupational stress among Muslim school administrators and senior teachers in a secondary school in Malaysia. It also investigates the Islamic techniques or methods they used in managing stress in their workplace.